Kajian Adverse Drug Reactions Terkait Interaksi Obat di Bangsal Rawat Inap Rumah Sakit Akademik UGM - Fivy Kurniawati; Nanang Munif Yasin; Amila Dina; Sanses Atana; Sarah Nabila Hakim (Faculty of Pharmacy, Universitas Gadjah Mada)
Adverse Drug Reactions (ADRs) is one of the causes of patient’s prolonged length of stay in the hospital and drug interactions can be included as one of the causes of the cause of ADRs. ADR related to drug interactions is a clinical problem that requires proper prevention. This study aimed to identify potential drug interactions also identify adverse drug reactions (ADRs) related to drug interactions in hospitalized patients at Universitas Gadjah Mada Teaching Hospital. This cross-sectional study used retrospective data collection through patient’s medical records from January to June 2018. Patients included in this study were all patients who received therapy more than two kind of drugs simultaneously treated in hospital wards of Universitas Gadjah Mada Teaching Hospital, Yogyakarta, Indonesia. The data collected were then analyzed descriptively. Drug interactions were analyzed using Drug Interaction Facts 2012 and Stockley. ADRs were analyzed by monitoring documented effects of patients with potential drug interaction. There were 115 of 362 patients (31.8%) with potential drug interactions. The total numbers of potential interactions that occur were 182 interactions. The most potential type of interaction was the interaction with moderate severity, with 115 interactions (63.2%). The majority of drug interactions occur through unknown mechanisms (54.4%). Actual ADR occurs in 3.3% patients who were 2 pediatric patients and 4 geriatric patients. This study can be a reference for drug interactions and ADRs as well as guide for pharmacist and healthcare in providing the right medication.